2016
DOI: 10.1016/j.tjem.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the C-MAC video laryngoscope to the Macintosh laryngoscope for intubation of blunt trauma patients in the ED

Abstract: ObjectivesWe aimed to compare the performance of the C-MAC video laryngoscope (C-MAC) to the Macintosh laryngoscope for intubation of blunt trauma patients in the ED.Material and methodsThis was a prospective randomized study. The primary outcome measure is overall successful intubation. Secondary outcome measures are first attempt successful intubation, Cormack–Lehane (CL) grade, and indicators of the reasons for unsuccessful intubation at the first attempt with each device. Adult patients who suffered from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 13 publications
1
40
1
6
Order By: Relevance
“…Video laryngoscopy generally improves the view of the glottis, without the need to align the airway axes to achieve a direct view from outside the patient's mouth, and can be considered as a rescue device. Nevertheless, the superiority of VL over DL for rescue intubation remains controversial …”
Section: Rescue Intubationmentioning
confidence: 99%
See 1 more Smart Citation
“…Video laryngoscopy generally improves the view of the glottis, without the need to align the airway axes to achieve a direct view from outside the patient's mouth, and can be considered as a rescue device. Nevertheless, the superiority of VL over DL for rescue intubation remains controversial …”
Section: Rescue Intubationmentioning
confidence: 99%
“…Although the use of VL has been increasing in the ED, there is a concern for the vulnerability of VL in patients with trauma where the airway could be contaminated by blood and vomitus . Although VL can provide better a glottic visualization compared to DL, VL should be used cautiously in this patient population according to the clinical practice guidelines for trauma management…”
Section: Special Circumstance: Patients With Traumamentioning
confidence: 99%
“…After a failed first intubation attempt in the emergency department, C-MAC device is more successful at second attempt than the direct laryngoscope 51. However, all the available RCTs comparing C-MAC videolaryngoscope and direct laryngoscope for emergency intubation show no benefit on the intubation success rate and intubation time with C-MAC videolaryngoscope 49,53,54. The detailed reasons for inconsistent findings obtained from the observational and randomized controlled studies are unclear, but several important issues may be considered.…”
Section: Commentsmentioning
confidence: 98%
“…Several observational and retrospective studies from emergency department, prehospital and ICU patients showed that a V-MAC or C-MAC device, compared with a direct laryngoscope, was associated with a significantly better visualization of the larynx and a higher proportion of successful intubations, especially for patients with predicted difficult intubations 4347. Furthermore, the use of C-MAC videolaryngoscope during emergency intubation was associated with significantly fewer esophageal intubations compared with direct laryngoscopy 43,48,49…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation